The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12877-021-02246-2
|View full text |Cite
|
Sign up to set email alerts
|

An examination of three prescribing cascades in a cohort of older adults with dementia

Abstract: Background Prescribing cascades are a source of inappropriate prescribing for older adults with dementia. We aimed to study three prescribing cascades in older Nova Scotians with dementia using administrative databases. Methods Cohort entry for Nova Scotia Seniors’ Pharmacare Program beneficiaries was the date of dementia diagnosis. Prescription drug dispensing data was extracted for inciting medication and second treatment (cholinesterase inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 55 publications
0
31
0
3
Order By: Relevance
“…Therefore, bladder anticholinergic agents such as oxybutynin, tolterodine, trospium and solifenacin are usually used to relieve urge incontinence which called AChEI-induced urinary incontinence prescribing cascade. 177 prescribing cascade is AChEI-induced rhinorrhea which is concomitant use of rhinorrhea medications to relieve side effects of AChEIs. The rhinorrhea medications consist of antihistamine, nasal anticholinergics and nasal glucocorticoids.…”
Section: Uncommon Adverse Effectsmentioning
confidence: 99%
“…Therefore, bladder anticholinergic agents such as oxybutynin, tolterodine, trospium and solifenacin are usually used to relieve urge incontinence which called AChEI-induced urinary incontinence prescribing cascade. 177 prescribing cascade is AChEI-induced rhinorrhea which is concomitant use of rhinorrhea medications to relieve side effects of AChEIs. The rhinorrhea medications consist of antihistamine, nasal anticholinergics and nasal glucocorticoids.…”
Section: Uncommon Adverse Effectsmentioning
confidence: 99%
“…]65 years) were more likely to receive; i) anticholinergics for urinary incontinence following SSRI initiation, 41 ii) ulcer drug therapy within 100 days of NSAID initiation, 91 iii) diuretic to treat betablocker induced oedema, 36 and, iv) thyroxine for hypothyroidism following amiodarone initiation. 87 Females were more likely to receive an antitussive for cough following ACEI initiation, 74 anticholinergic medication for urinary incontinence following acetylcholinesterase inhibitor 24,30 and SSRI initiation, 41 and levothyroxine following amiodarone initiation. 87 Differential associations were identified for initial medication dosage in nine studies.…”
Section: New Medication(s) Prescribedmentioning
confidence: 99%
“…Several studies reported stratified results by dosage, 5,7,28,29,39 concomitant medication use or polypharmacy, 7,40,44,87,106 duration, 32,96 comorbidity, 36,38,40,44 race 34 and nursing home residence. 26 For other studies, analyses were adjusted by age, 20,22,30,52,71,91,121 sex, 20,22,30,52,71,74,84,121 race, 22,121 dose, 52,71 nursing home residence, 22 concomitant medication or polypharmacy, 22,52,71 comorbidity, 121 with some studies conducting adjusted analyses but not reporting the independent association of these covariates. 23,27,31,90,119,120 Length of follow up ranged from one month 55,93,109,…”
Section: Introductionmentioning
confidence: 99%
“…Many prescribing cascades have been identified and their potential impact on patients described [3][4][5][6][7][8][9]. Much of the existing research on prescribing cascades has used healthcare administrative data to assess their prevalence and impact [10][11][12][13][14][15][16]. Resources have been identified that can help people prevent, detect and reverse prescribing cascades but there remain outstanding knowledge gaps regarding both clinicians and patients' experiences with identifying and addressing them as well as how and why prescribing cascades occur in practice [9,17,18].…”
Section: Introductionmentioning
confidence: 99%